Mercado de crédito de carbono: evolução no Brasil - Guimarães, Vinícius Silva (Brasil, 2024)
The carbon credit market has emerged as an essential tool in mitigating climate change, encouraging the reduction of greenhouse gas emissions. This work explores the emergence and evolution of this market in the world and in the Brazilian context. The study examines the history of the carbon credit market in Brazil, from the first emission reduction projects to recent policies and trends. The main purpose of this research is to examine the current state of evolution of the carbon credit market. To achieve this objective, the study focuses on specific areas, such as the origin and development of the carbon credit market in Brazil, as well as the explanation of what the carbon credit market is and its performance in Amazonia. Regarding the methodology of this study, it is based on a narrative literature review, with the aim of tracing the development of the carbon credit market in Brazil. Data collection was conducted through research into academic articles, government reports, documents from international organizations and other pertinent sources related to the carbon credit market in the context of Brazil. The analysis of the collected data was carried out qualitatively. This time, we identified that the main factors that drove the growth of the carbon credit market in the country were private investments and international partnerships. Therefore, it was clear that the functioning of the market is being carried out on a voluntary basis and the project to make regulation viable is being processed in the national congress.